Physical, Virtual and Symbolic Spaces of a Heterodox Friendship: Salvador Novo and Xavier Villaurrutia - Cañedo, César (Estudios LGBTIQ+, Comunicación y Cultura, 2022)
The purpose of this paper is to analyze the codes of intimacy and queerness that Mexican poets Xavier Villaurrutia and Salvador Novo built together thanks to their heterodox and youthful friendship. To this end, the analysis of spaces as producers of social experience and intimacy is taken as an axis, and these will be thought of in a broad sense that allows me to unravel the poetic space as a symbolic space that both transform into a space of queerness and mutual confidences; as well as to observe certain physical spaces, such as the «studios» that Villaurrutia and Novo came to share, and the configuration of the virtual space of the letters as a dialogue for understood people. As textual sources I take mainly Villaurrutia’s Letters to Novo [1935-1936], Novo’s memoir La estatua de sal (c. 1945), and some poems by both in which the dedications, allusions, shared metaphors and the confidential code they articulate are remarkable. In all these spaces, strategies of effeminacy will be deployed as discursive, poetic, and behavioral strategies; I divide these strategies into street effeminacy (embodied practices) and textual effeminacy (discursive, metaphorical, and symbolic practices) with the intention of reflecting on how an aesthetic, an ethics of mutual care and initiation, and a heterodox filial and sexual poetics developed in the first decades of the twentieth century in Mexico.